A Multimodal Approach to the Management of Neuroendocrine Tumour Liver Metastases - Basuroy, Ron (Hindawi Publishing Corporation, 2012)
Neuroendocrine tumours (NETs) are often indolent malignancies that commonly present with metastatic disease in the liver. Surgical, locoregional, and systemic treatment modalities are reviewed. A multidisciplinary approach to patient care is suggested to ensure all therapeutic options explored.